Vedaz Event Management Booking System with TOTP - Morgan, Piriyah; Md Salleh, Dr.Siti Fadzlun (Applied Information Technology And Computer Science, 2025)
Modern event management demands efficient solutions due to evolving customer expectations and technological advancements. This requirement is met by the Time-based One-Time Password (TOTP) authentication feature of the Vedaz Event Management Booking System (VEMBS). With the help of object-oriented programming and TOTP, this web-based platform improves security and efficiency when handling bookings for events. Secure user identification, extensive data management, and a smooth booking process are all guaranteed by the Vedaz Event Management Booking System. This project proposes a secure online booking system designed using the Object-Oriented System Design (OOSD) methodology. Key features include email verification, Time-Based One Time-Password using Google Authenticator, session management, role-based access control, strong password, data encryption, and secure payment